Abstracts (Edited By Dr. Qasim Lateef Chaudhry) - Chaudhry, Qasim Lateef (Pakistan Journal of Ophthalmology, 2018)
Vitrectomy with Internal Limiting Membrane Peeling versus No Peeling for Idiopathic Full-Thickness Macular Hole Cornish KS, Lois N, Scott NW, Burr J, Cook J, Boachie C, Tadayoni R, Cour M, Christensen U, Kwok AKH Ophthalmology 2014; 121: 649-55. Collaborative Retrospective Macula Society Study of Photodynamic Therapy for Chronic Central Serous Chorioretinopathy Lim JI, Glassman AR, Aiello LP, Chakravarthy U, Flaxel CJ, Spaide RF Ophthalmology 2014; 121: 1073-8. Antibiotic Choice for the Prophylaxis of Post-Cataract Extraction Endophthalmitis Rudnisky CJ, Wan D, Weis E Ophthalmology 2014; 121: 835-41. Collagen Cross-Linking in Progressive Keratoconus; Three Year Results Wittig-Silva C, Chan E, Islam FMA, Wu T, Whiting M, Snibson GR Ophthalmology 2014; 121: 812-21